1974
DOI: 10.1139/v74-157
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Nitrogen Heterocycles. VII. Reactions of some Tricyclic Heteroaromatic Cations in Basic Solutions

Abstract: Pseudobase formation and methoxide ion addition have been investigated spectroscopically for some N-methylacridinium, -phenanthridinium, and -benzoquinolinium cations. Susceptibility to nucleophilic attack decreases in the order 10-methylacridinium (pKnorr = 9.86) > 5-methylphenanthridinium (pKnoa = 11.94) > 1-methyl-5,6-benzoquinolinium = 1-methyl-7,8-benzoquinolinium (~Knorr > 14). A qualitative correlation of pKnorr with loss of resonance energy upon pseudobase formation is shown to exist. For the 9,lO-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…The pseudo-base adduct does not absorb at the chosen excitation wavelength and the observed emission intensity was zero above pH 13.5. An effective dissociation constant of 16 mM (9 2), equivalent to pK OH = 12.2 [34] is in good agreement with related literature values for ground-state ions, [46]. Thus the red europium emission is independent of pH over the range 2-9 but falls in intensity by a factor of \ 200 as the pH rises to over 13.…”
Section: Quenching Of the Singlet Excited State By Anionssupporting
confidence: 89%
See 1 more Smart Citation
“…The pseudo-base adduct does not absorb at the chosen excitation wavelength and the observed emission intensity was zero above pH 13.5. An effective dissociation constant of 16 mM (9 2), equivalent to pK OH = 12.2 [34] is in good agreement with related literature values for ground-state ions, [46]. Thus the red europium emission is independent of pH over the range 2-9 but falls in intensity by a factor of \ 200 as the pH rises to over 13.…”
Section: Quenching Of the Singlet Excited State By Anionssupporting
confidence: 89%
“…It has been established that N-methylphenanthridinium ions are attacked at C-6 by the hydroxide ion, in a reversible reaction [46] that leads to the disappearance of the longest wavelength absorption band as the conjugation length is reduced, ( 10). With [Eu 16a] + , addition of KOH over the pH range 10-13.5, led to a decrease in the europium emission intensity (u exc 380 nm, u em 594 nm) as reversible C O bond formation occurred.…”
Section: Quenching Of the Singlet Excited State By Anionsmentioning
confidence: 99%
“…It can be mentioned here that the C, position of sanguinarine iminium ion (structure I) is such a high electrophilic centre that even a very poor nucleophilic solvent can make an addition to that position. Similar studies have been reported by several workers (Bunting and Meathrel, 1974;Kano et al, 1986Kano et al, , 1987Zhou et al, 1988) who have found that the electrophilicity of 10-methylacridinium and 10methyl-9-phenylacridinium cations is so strong that nucleophiles such as hydroxide and alkoxide anions attack the carbon atom at the 9 position of the acridinium ring to give the corresponding pseudo bases. Reversibility of sanguinarine from structure 11,111 and IV to structure I also has been confirmed by spectrophotometric (Figs.…”
Section: Discusslonsupporting
confidence: 88%
“…Bunting and Meathrel [8] report the same value for λ max and a value of log ε = 4.28. Fluorescence of the MA + cation is strongly quenched by I − , Br − , and SCN − ions.…”
Section: Resultsmentioning
confidence: 74%